2020
DOI: 10.3390/ijerph17176141
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Frail Older Adults with Foot Pain in a Spanish Population: An Observational Study

Abstract: Frailty is a condition that can increase the risk of falls. In addition, foot pain can influence older adults and affect their frail condition. The main objective was to measure the frailty degree in older adults in a Spanish population with foot pain from moderate to severe. Method: This is a cross-sectional descriptive study. A sample of people older than 60 years (n = 52), including 26 males and 26 females, were recruited, and frailty disability was measured using the 5-Frailty scale and the Edmonton Frailt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
(40 reference statements)
2
17
0
Order By: Relevance
“…It is calculated as the ratio of the number of deficits present in the individual to the number of total deficits considered [ 28 ]. The Edmonton Frail Scale (EFS) [ 29 ], its recent validated short version (EFS-SF) [ 30 , 31 ], the Fatigue, Resistance, Ambulation, Illnesses, and Loss of Weight (FRAIL) Score [ 32 ], the Geriatricians’ Clinical Impression of Frailty (GCIF) scale [ 33 ], and the Clinical-Functional Vulnerability Index-20 (IVCF-20) [ 34 ] are other approaches able to identify frailty.…”
Section: Introductionmentioning
confidence: 99%
“…It is calculated as the ratio of the number of deficits present in the individual to the number of total deficits considered [ 28 ]. The Edmonton Frail Scale (EFS) [ 29 ], its recent validated short version (EFS-SF) [ 30 , 31 ], the Fatigue, Resistance, Ambulation, Illnesses, and Loss of Weight (FRAIL) Score [ 32 ], the Geriatricians’ Clinical Impression of Frailty (GCIF) scale [ 33 ], and the Clinical-Functional Vulnerability Index-20 (IVCF-20) [ 34 ] are other approaches able to identify frailty.…”
Section: Introductionmentioning
confidence: 99%
“… 22 An observational study of elderly participants in Spain showed a significant correlation between cognition and frailty. 23 During the aging process, coordination among the systems declines, and the original balance control process based on body reflexes relies more on cognitive function. 24 Decreased cognitive integration function may lead to deviations in judgment of the surrounding environment.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Navarro-Flores recently found that using more than 5 different medications on a regular basis is correlated with the fragility in older participants, which may increase the risk of falls. 23 Findings by Bloch and Woolcott JC both showed that gait and balance function may be influenced by combined use of multiple drugs, especially psychotropic medication. 32 , 33 Good control of vascular risk factors and rational prescription of medications remains important to patient health and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Harrison et al 52 reported in 100 diabetic patients that only 20% use appropriate footwear, according to measurement length and width. Furthermore, several studies have reported an increase in podiatric pathologies with aging 53 , 54 . In our study, the podiatric examination detected that 88.68% of the participants present some type of podiatric pathology.…”
Section: Discussionmentioning
confidence: 99%